PENGARUH HARGA, LOKASI PENJUALAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DODOL - Winda Silviana; Saidun Hutasuhut (Universitas Negeri Medan, 2017)
This study aims to determine the effect of variables of price, sales locations and product quality toward dodol purchase decisions in Tanjung Pura Langkat. The number of population in this study are 7000 consumers and the number of samples determined by Slovin formula as many as 100 people.Sampling technique used is simple random sampling. Data collected by Likert scale questionnaire. Questionnaire first tested the validity and reliability. Further data are analyzed by multiple regression. Hypotheses were tested by t-test and f test with data classical assumption tested first. Research findings are partially obtained that the price, product quality positively and significantly influence the purchase decision. However, the sales location has no effect towards the purhacasing decision. While joint test of price variables, location of sales and product quality simultaneously have a positive and significant effect on purchasing decision of dodol. 49,4% variation in purchases of dodol is explained by the three variables. The remaining 50,6% is explained by other variables outside the research model. Keywords : Price, Location, Product Quality, Purchase Decision